Design and Development of Mini Model for Mini Tempeh Packaging Machine - Bin Ahmad Shuffir, Emir Haikal; Mohd Harun, Dalila (Progress in Engineering Application and Technology, 2021)
Automatic process plays an important role in packaging food in industry because it can be produced in large quantity and shorter time taken. In this project, Solid work software will be used to design mini model folded and rubber band part of Mini Packaging Machine. Other than that, Arduino uno also use to run the automatic system for this mini model that support by the stepper and servo motor. Material used to create mini model prototype were playwood, rubber, mini gear and metal plate. The selected material for folded and rubber band part is AISI 316 Stainless steel and it was tested for static test to check whether the material suitable or not for this prototype. Simulation result shows that AISI 316 stainless steel is suitable material for folded and rubber band part because the strength AISI 316 Stainless steel value was 1.724+008 N/m². Besides that, the cost of the material must be suitable as to minimize the cost.